Use of Possessive Pronouns in English and Uzbek Languages (Eurasian Journal of Learning and Academic Teaching, 2022)
The article describes the use of possessive pronouns in English and Uzbek languages. The peculiarities of the category of possession in languages belonging to different families have been considered